Health Aid and Infant Mortality - Newhouse, David Locke (IMF Working Papers; Working Paper, 2007)
This paper examines the relationship between health aid and infant mortality, using data from 118 countries between 1973 and 2004. Health aid has a statistically significant effect on infant mortality: doubling per capita health aid is associated with a 2 percent reduction in the infant mortality rate. For the average country, this implies that increasing per capita health aid by USD 1.60 per year is associated with 1.5 fewer infant deaths per thousand births. The estimated effect is small, relative to the targets envisioned by the Millennium Development Goals.